Decline in genital warts diagnoses among young women and young men since the introduction of the bivalent HPV (16/18) vaccination programme in England: an ecological analysis. (30th June 2016) - Canvin, M; Sinka, K; Hughes, G; Mesher, D
Abstract : Background: For several decades, diagnoses of genital warts at genitourinary medicine (GUM) clinics in England had been increasing. In 2008, a national human papillomavirus (HPV) vaccination programme was introduced using the bivalent vaccine (types 16 and 18 only). A decrease in genital warts was not anticipated. However, rates of genital warts in GUM clinics have declined significantly since the introduction of the vaccine. Methods: Using data from GUM clinics across England, we analysed rates of genital warts by age, gender, sexual orientation and estimated vaccine coverage. Results: The reduction in rates of genital warts diagnoses at GUM clinics between 2009 and 2014 was 30.6% among young women aged 15–19 years and 25.4% among same age heterosexual young men. Overall there was an association showing higher warts reduction with increasing vaccination coverage with the largest declines in warts diagnoses observed in young women aged 15 years (50.9%) with the highest vaccination coverage. No such declines were observed in men who have sex with men (MSM) of the same age. Conclusion: The results of these ecological analyses are strongly in keeping with the bivalent HPV vaccine providing modest protection against genital warts.